Native copper formation in mine-prop wood from Cyprus illustrates displacive growth by force of crystallization. (January 2020) - Vissers, Reinoud L.M.; Wolterbeek, Timotheus K.T.
Abstract: A long-standing issue in the study of metamorphic rocks concerns the question in how far replacement of the protolith assemblage during the growth of metamorphic porphyroblasts is accompanied by the additional operation of a displacive mechanism due to an alleged 'crystallization force' exerted by the growing porphyroblast. Whilst in few cases a component of displacive growth can be corroborated, unequivocal criteria to identify such displacements are lacking. It follows that the concept of a so-called 'crystallization force' is surrounded by uncertainties on the viability and operation of displacive growth in natural systems. We investigate the growth of Cu porphyroblasts in a sample of mine-prop wood from a Bronze Age copper mine in Cyprus. The pit prop became infiltrated with copper-saturated, polluted mine water during collapse of an ancient mine gallery. The microstructures associated with the copper porphyroblasts strongly indicate displacive growth, whilst the matrix wood has not been affected by any externally imposed deformation. We suggest that the displacement microstructures associated with the copper porphyroblasts substantiate the existence of 'crystallization forces'. Highlights: Metamorphism involving a volume increase may cause a 'force of crystallization'. Criteria to assess displacive growth of porpyroblasts are often inconclusive. The role in natural rocks of a 'crystallization force' is difficult to prove. Mine-prop wood from an ancient mine in Cyprus contains copper porphyroblasts. Wood microstructure implies porphyroblast growth via a 'crystallization force'.